2018
DOI: 10.1590/1413-812320182310.24582016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados ao uso de álcool durante a gestação em uma maternidade de Goiás, Brasil Central

Abstract: Resumo O objetivo deste artigo é estimar a prevalência e os fatores associados ao uso de álcool durante a gestação. Estudo de corte transversal em uma amostra de 361 gestantes de um serviço de referência à assistência ginecológica e pré-natal. Os dados relacionados às características sociodemográficas, uso de álcool e potenciais fatores associados foram coletados por meio de entrevista face a face. Análise de regressão de Poisson com variância robusta foi utilizada para verificar os fatores associados ao desfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
3
9
0
11
Order By: Relevance
“…Regarding the prevalence found for alcohol consumption, specific studies in different regions of the country, such as Rio Grande do Sul and Rio de Janeiro (25)(26) , found similar results to the present research. Other specific studies found a higher prevalence, such as 23.1% in Minas Gerais and 17.7% in Goiás (13,27) . However, it is worth mentioning that the direct comparison between prevalence of all studies in this area is limited, since the form of data collection for both smoking and alcohol consumption was not uniform, differing significantly between each survey.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Regarding the prevalence found for alcohol consumption, specific studies in different regions of the country, such as Rio Grande do Sul and Rio de Janeiro (25)(26) , found similar results to the present research. Other specific studies found a higher prevalence, such as 23.1% in Minas Gerais and 17.7% in Goiás (13,27) . However, it is worth mentioning that the direct comparison between prevalence of all studies in this area is limited, since the form of data collection for both smoking and alcohol consumption was not uniform, differing significantly between each survey.…”
Section: Discussionmentioning
confidence: 83%
“…Some individual characteristics have been associated with the habit of drinking alcohol and smoking during pregnancy. Alcohol consumption was identified as higher among pregnant women with depression, with less social support, whose pregnancy was not planned and without knowledge about the negative effects of alcohol on the fetus (12)(13)(14) . As for tobacco consumption, a higher prevalence has been identified among women with less education and income, with black skin color, with depression and among adolescents and multiparous women (15)(16) .…”
Section: Introductionmentioning
confidence: 99%
“…Em Maringá, Paraná, 11 a prevalência levantada foi de 6, 1%; em São Luís, Maranhão, 12 22,32%; e no estado de Goiás, de 17,7%. 13 Em todas as regiões observa-se alta prevalência desse consumo durante o período gestacional.…”
Section: Discussionunclassified
“…Concerning specific behaviors and morbidities, knowledge, and prevention of toxoplasmosis 46 , factors associated with gestational breast cancer 47 , cytopathological test 48 , and rapid an- ti-HIV test 49,50 , vaccination coverage among puerperae and pregnant women 51,52 , alcohol 53 and medication 54 use, folic acid supplementation 55 , and severe low back pain 56 . The nutritional status of pregnant women 57,58 and its association with baby weight at birth and prematurity 59,60 also appear among the topics addressed.…”
Section: Thematic Lines and Sample/data Originmentioning
confidence: 99%